Is there a role for the platelet-to-lymphocyte ratio in chronic lymphocytic leukemia?. (5th October 2018) - Bakouny, Ziad; Rassy, Elie El; Yared, Fares; Lutfallah, Antoine Abi; Ghosn, Marwan; Farhat, Fadi; Kattan, Joseph
Aim: The rationale for platelet-to-lymphocyte ratio (PLR) in chronic lymphocytic leukemia (CLL) is that both the platelet and lymphocyte counts are affected by the CLL pathogenesis and could influence treatment decision-making.Methods: Demographic and clinical data of CLL patients diagnosed at our institution between 1989 and 2013 were collected. Cox regression models were used to evaluate the role of PLR in the duration of watchful waiting, postdiagnosis survival and postchemotherapy survival.Results: The data of 100 patients with CLL were reviewed for this study. The PLR correlated only to watchful waiting in the univariable analysis (Hazard ratio = 0.48 [0.32–0.73]; p = 0.018). In the multivariable analysis, the duration of watchful waiting was determined by Binet staging and lymphocyte count (p < 0.001). The postdiagnosis survival was determined by age (p = 0.002) and lymphocyte count (p = 0.010).Conclusion:  The PLR did not seem to act as a prognostic biomarker for CLL. Lay abstract: Patients with chronic lymphocytic leukemia (CLL), an incurable but often indolent hematological cancer, often have increased lymphocytes and decreased platelets. We investigated whether the ratio of platelet-to-lymphocyte count can be used as a biomarker to predict the prognosis of patients with CLL. An increase in the platelet-to-lymphocyte ratio was found to be related to a decrease in the duration of watchful waiting (the duration between the diagnosis of CLL and the administration of chemotherapy to the patient). However, the ratio was not found to be related to patient survival and therefore, based on this study, it cannot be considered as a biomarker for the prognosis of CLL.